A study of electrodeposited thin tin films in cycling in aprotic solvents - Globa, N. I.; Kublanovsky, V. S.; Nikitenko, V.N.; Milovanova, O. I. (Reports of the National Academy of Sciences of Ukraine, 2014)
Electrodeposited tin films, obtained from complex (citrate, tartrate and citrate-trilonate) electrolytes, have been investigated by the methods of potentiodynamic and galvanostatic cycling in an aprotic ethylene carbonate – dimethyl carbonate solvent. It has been shown that the nature of ligand affects greatly the electrochemical characteristics, specific capacity of tin films, and efficiency of their cycling in lithium current sources. The most stable electrochemical characteristics and charge-discharge conditions are peculiar to tin films deposited from a citrate electrolyte. The specific capacity of these films in the first cycles is 500 mA · h/g and decreases subsequently to 400–420 mA · h/g during the cycling, which corresponds to a loss of 1.1–1.3% within a cycle.